(untitled) (Italian Journal of Public Health, 2009)
Rare diseases (RD)s are a serious public health problem and represent unique challenges in many Countries, including EU and USA. RDs are life-threatening or chronically debilitating diseases characterized by low prevalence; this entrains limited resources as well as insufficient knowledge available for most of these individual diseases. However, RDs are numerous (possibly more than 6,000) and overall a considerable number of citizens can be affected. Special combined efforts are needed to reduce the global population effects of RDs, such as early mortality and a considerable reduction in an individual’s quality of life.